PENERAPAN MODEL WATERFALL DALAM MERANCANG APLIKASI PEMILIHAN SISWA TELADAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Hidayatun, Nunung; Murtina, Hidayanti; Susafa’ati, Susafa’ati (INTI Nusa Mandiri, 2024)
By having exemplary students, it is hoped that students at school will have good role models in all aspects. Unfortunately, subjective selection because it is done using voting can lead to unhealthy competition. So far, the selection of exemplary students begins with the selection of students with the highest average scores, then looks at the student's activity and record of violations which culminates in a vote carried out in the exemplary student selection meeting. Voting at the end of the election can cause the selection of exemplary students to no longer be objective and no longer fair. The application design will use the waterfall method by implementing the SAW method as a method used to help make decisions. The criteria used are 7 criteria in accordance with school policy and the results of this analysis, first the system is able to record all students who will be alternative exemplary students and also the criteria set in accordance with school policy. Second, by implementing a decision support system using CBIS, it can minimize the objectivity and complexity of stakeholders in making decisions and can increase data accuracy. Third, based on the management using this decision support application, an alternative ranking of exemplary students was obtained with the first alternative position being Siska Azzahra Shafa with a total score of 19,790, the second alternative being Andrawan Erlang Padana with a total score of 19,654 and the third being Ichsan Sandi with a total score of 19,645.